2020
DOI: 10.7759/cureus.7362
|View full text |Cite
|
Sign up to set email alerts
|

Osgood-Schlatter Lesion Removed Arthroscopically in an Adult Patient

Abstract: Osgood-Schlatter disease is a traction apophysitis of the tibial insertion of the patellar tendon. It consists one of the most common causes of knee pain in adolescents and usually presents in young males and it is considered a self-limiting condition. Although the symptoms disappear after the closure of the growth plate in most cases, in some patients they may persist. A variety of conservative treatments are used in most cases, however surgical intervention can be successful for patients who have intolerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…These portals reduce the risk of damage to the infrapatellar fat pad, anterior horn of the meniscus, and intermeniscal ligament. 9 Bursoscopic surgery also facilitates the easy removal of ossicles, located distal to the deep infrapatellar bursa. One potential disadvantage of bursoscopic surgery, especially in the debridement of the tibial tuberosity, 4 is the limited working space.…”
Section: Discussionmentioning
confidence: 99%
“…These portals reduce the risk of damage to the infrapatellar fat pad, anterior horn of the meniscus, and intermeniscal ligament. 9 Bursoscopic surgery also facilitates the easy removal of ossicles, located distal to the deep infrapatellar bursa. One potential disadvantage of bursoscopic surgery, especially in the debridement of the tibial tuberosity, 4 is the limited working space.…”
Section: Discussionmentioning
confidence: 99%
“…This scanner is wrapped into a sterile plastic bag and available during the operation. Tsakotos et al 8 reported that fluoroscopic control was necessary after the arthroscopic Fig 10 . Nano-arthroscopic view of the patient's left knee during excision of ossicles (OS). A 2.0-mm arthroscopic punch is inserted from the medial working portal.…”
Section: Discussionmentioning
confidence: 99%
“…Tsakotos et al. 8 reported that fluoroscopic control was necessary after the arthroscopic excision of the osscle. This technique using ultrasonography is also superior compared with past reports in terms of radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…La mayoría de las opciones quirúrgicas de la enfermedad de Osgood-Schlatter incluyen procedimientos abiertos, actualmente se efectúa la escisión artroscópica directa. 3…”
Section: Figuraunclassified